Whole genome sequencing of non-aureus Staphylococcus species from poultry barn bioaerosols across Alberta reveals circulation of isolates with multiple antibiotic resistant genes and disinfectant resistant genes - Awais Ghaffar; Karen Liljebjelke; Sylvia Checkley; Frank van der Meer; Muhammad Farooq; Heshanthi Herath Mudiyanselage; Mohamed Faizal Abdul-Careem (Journal of Global Antimicrobial Resistance)
Objectives: Poultry environment has vast variety of bacterial species and non-aureus Staphylococcus species (NASS) are predominantly found. Various NASS are normal inhabitant of gastrointestinal tract and skin of chickens. The study objective was to isolate and identify NASS from bioaerosols of layer chicken barns across Alberta, leading to the phenotypic and genotypic antimicrobial resistance (AMR) profiling of the isolated bacterial colonies. Methods: A total of 15 barns were sampled in this study with an XMX-CV microbial air sampler. Phenotypic AMR profiles were determined using the Sensititre® broth microdilution method on the standard CMV3AGPF plates and whole genome sequencing (WGS) was conducted to confirm the species and AMR genes. Results: Seven Staphylococcus equorum, 5 Staphylococcus shinii, 1 Staphylococcus pseudoxylosus, 1 Staphylococcus cohnii, and 1 Staphylococcus gallinarum isolates were confirmed and identified by WGS and comparative genomic analysis. One of the S. equorum isolate was genetically highly divergent from the remaining isolates of the study. The phenotypic susceptibility profile showed 73.3% (11/15) of the isolates were resistant to lincomycin, 66.7% (10/15) were resistant to tetracycline, 33.3% (5/15) were resistant to streptomycin, 20% (3/15) were resistant to erythromycin, and 6.3% were resistant to gentamicin. A total of 10 antimicrobial resistance genes (ARGs) for antibiotics and 1 gene encoding resistance to disinfectants were detected among the study isolates by WGS. Conclusions: Normal bioaerosol microflora having ARGs may lead to reduced therapeutic effectiveness of antibiotics in poultry and these ARGs can be a source of serious public health concern.